A Comprehensive Set of Mobile Services Supporting Education Process. (13th May 2015) - Samochadin, Alexander; Raychuk, Dmitry; Nosnitsyn, Semen; Khmelkov, Igor
Abstract: Nowadays many universities are using Internet and mobile services to support various activities in education process. However, these services often provide incomplete functionality and are not connected to each other. To address this problem, the paper overviews existing services and requests from students and academic staff members and proposes requirements for a new system. Based on the analysis, the paper proposes a comprehensive set of seven mobile services: attendance monitoring, performance monitoring, timetable management, interactive teaching, testing and exams, course materials, distribution of course tasks and group work. The paper presents architecture of the system based on Mobile Device Management followed by a description of mobile services' functionality.